Comparison of magnetic resonance imaging and high-resolution ultrasound for the diagnosis of pathologies of the peripheral nerve - Bassam Alkhalifah (Wolters Kluwer Medknow Publications, 2023)
The study was done to evaluate high-resolution ultrasound with Magnetic Resonance Imaging (MRI) for the diagnosis of peripheral nerve pathologies. Ultrasound examination and MRI were performed for selected cases, and their sensitivity and specificity were compared. Ultrasound was found to detect peripheral pathologies with greater accuracy as compared to MRI. Also, ultrasound was found to have higher sensitivity and specificity than MRI. It was concluded that ultrasound is a better adjunct tool for the diagnosis of peripheral nerve lesions when compared with MRI.